Jaringan Digital dan Pengembangan Kewirausahaan Sosial Buruh Migran Perempuan - Eko Wahyono; Lala M. Kolopaking; Titik Sumarti M. C.; Aida Vitayala S. Hubeis (FISIP Universitas Atma Jaya Yogyakarta, 2019)
The purpose of this study is to analyze the use of digital technology and social networks in post-returning female migrant workers’ social entrepreneurship. This study uses a qualitative approach by conducting in-depth interviews, FGDs, and observations. The results show that digital technology and social networks have an important role in the process of developing entrepreneurship in the villages of origin of the migrant workers. Meanwhile, the challenges are the lack of technological infrastructure, capital circulation, and social marketing strategies in therural area.